Efficient Channel Allocation for Load Balancing in Wireless Mesh Networks - Sheenam; Chadha, Raman (2024 International Conference on Integrated Circuits, Communication, and Computing Systems (ICIC3S), 2024)
Wireless Mesh Networks, has advantages over existing wireless mechanisms, and will be the mainstay of future-generation wireless networking. In this subject, a lot of difficult technological problems are still unresolved. The load balancing algorithm represents one of the primary issues with WMNs. Because of the expected high volume of traffic in a WMN, load balancing becomes essential. Load balancing increases network scalability and availability. Load balancing is one way to outspread the lifespan of a mesh network. Because there are usually several paths to the target node, load balancing is the simplest technique to upgrade the network throughput and minimize the congestion in a WMN. To gain a better understanding of the load-balancing issues associated with WMNs, this study provides a comprehensive review of how load is distributed over the different channel.